Visual patterns and the development of creativity and functional reasoning - Débora Tavares; Isabel Cabrita (European Teacher Education Network, 2014)
Despite the importance of creativity, its development has not been a priority of Mathematics, especially in what concerns non-‐gifted students. Students often reveal many difficulties in functional reasoning. Some studies have concluded that an adequate exploration of visual patterns may contribute to overcoming these difficulties. Thus, we developed a qualitative case study aiming to find out if the exploitation of tasks focused on visual patterns contributed to the development of creativity and functional reasoning in 8th grade students. It was found that students improved their performance in tasks whose resolution required the mobilization of functional reasoning and their creativity. Some of the beliefs and/or conceptions about creativity have also evolved positively.